Subcortical contribution to late TMS-induced I-waves in intact humans - Cirillo, John; Perez, Monica A. (Frontiers in Integrative Neuroscience, 2015)
Paired-pulse transcranial magnetic stimulation (TMS) of the human motor cortex results in consecutive facilitatory motor evoked potential (MEP) peaks in surface electromyography. It has been proposed that early and late MEP peaks involve different mechanisms of action, however, little is known about the characteristics of the later peaks. Using paired-pulse TMS over the hand motor cortex at different test (S1) and conditioning (S2) interstimulus intervals and intensities we examined early (first) and late (second and third) MEP peaks in a resting finger muscle. We demonstrate that the third peak had reduced amplitude and duration compared to the second, regardless of the S1 intensity. Higher S2 intensity increased the amplitude of the third but not the second peak, suggesting that the third peak had a higher threshold. The interval between the second and third peak was longer than between the first and second peaks in all conditions even though all peaks had similar latency dispersion. No differences were found in the amplitude, duration, and threshold of the first and second peaks. A threshold electrical S2 over the cervicomedullary junction facilitated the second and third but not the first peak similarly to TMS. Our results indicate that the third MEP peak is smaller and has higher threshold than the second peak and the similarities between the first and second peaks suggest that this is less likely explained by a reduced effectiveness in recruitment. We argue that subcortical pathways might contribute to differences found between late TMS-induced peaks in intact humans.